Suelos expansivos su estabilizacion con cal - Garcia, Juan Julio Jorge Menéndez (1973)
A study of geotechnical characteristics and lime stabilization of two samples of typical expansive "massapés" soils from the "Recóncavo Baiano", State of Bahia, Brazil. Experimental work included mineralogical analysis of clay fraction (X-ray diffractometry and D.T.A.), chemical testing, expansibility (Protuguese LNEC test), expansion pressure, Linear shrinkage, compressibility and triaxial compression tests. The mechanisms of lime stabilization of massapés soils were analyzed through the effect of lime on clay minerals, Atterberg limits, expansion, shear strength parameters, and compressibility. Linear Shrinkage was compared to Plastic Index accordeap to existing correlations. Most adequate lime porcentage for stabilizing massapé soil samples was determined and reference made to possibilities of using the pH method for such a determination.